Konsep An-Nafs dan Ar-Ruh - Sarimulia, Indah; Lia, Nur; Lestari, Retno Ayu; Lubis, Ramadhan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
An-Nafs and Ar-Ruh are important concepts in Islamic philosophy related to the human soul and spirit. An-Nafs refers to the soul which includes the psychological, emotional and spiritual aspects of humans. In the Islamic view, an-nafs has various levels, starting from nafs al- ammarah (a soul that tends to evil) to nafs al-mutmainnah (a soul that is serene and full of peace). Meanwhile, ar-ruh refers to the spirit which is an element given by God to every living creature which is the link between the physical body and spiritual life. Spirits cannot be seen or explained in material terms, but are believed to be the source of life for the body. This concept has a central role in human understanding in Islam where the two interact with each other to shape a person's spiritual and moral state, therefore understanding an-nafs and ar-ruh is important in the process of self-development and achieving life goals in accordance with religious teachings.